Mini review on nanoimmobilization of lipase and cellulase for biofuel production. Issue 2 (17th February 2020) - Rao, Ashok; Sathiavelu, A.; Mythili, S.
ABSTRACT: Nanomaterials have been used in various applications such as sensors, biofuel cells and biodiesel production. Various nanomaterials provide a high surface area-to-volume ratio and can be fabricated with enzymes as sensors for assay and in electrodes for electricity generation in biofuel cells. The methods of nanomaterial synthesis, analytical techniques for loading of enzymes, and fabrication of enzymes with nanomaterial along with the effect of enzyme immobilization on its activity have been discussed. In this mini-review article we concentrate on the current trends leading to various effects on immobilization of enzymes with nanomaterial. We focus mainly on enzymes used in hydrolysis of lignocellulosic agro-waste to produce bioalcohols by a fermentation process and enzymes used in transesterification reactions for biodiesel production. The current status of nanomaterial as an integral part of sustainable enzymatic biofuel production is discussed.